Effect of the Addition of Carnauba Wax on Physicochemical Properties of Chitosan Films - Francisco Klebson Gomes dos Santos; Karyn Nathallye de Oliveira Silva; Talisson Davi Noberto Xavier; Ricardo Henrique de Lima Leite; Edna Maria Mendes Aroucha (Materials Research, 2017)
Films and edible coatings of natural polymers have been proposed as an attractive alternative for conventional plastic packaging because of their excellent biodegradability and biocompatibility. However, natural polymers, like chitosan, are hydrophilic and present poor water barrier properties. The addition of wax or other hydrophobic substances decreases water permeability of natural polymers but can increases their opacity.The objective of this work was to produce biofilms based on chitosan and different concentrations of carnauba wax and analyze their optical and barrier properties. The films were obtained by dissolving chitosan in acetic acid. Carnauba wax was incorporated into film-forming solutions at0, 15, 30, 40 and 50% (w/w). The opacity increased with higher concentrations of wax, the film with 50% of wax showed the highest value with an increase of 10.5% compared to the control film. The water vapor permeability decreased from 2.73 g.mm/kPa.m2.h (0% of wax) to 0.77 g.mm/h.kPa.m2 (40% of wax). The solubility decreased to about 60% over the control films, and the contact angle increased from 53º to 83º, in film with 0 and 50% of wax, respectively.